2022
DOI: 10.1094/pdis-08-21-1745-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Fusarium Wilt Disease Caused by Fusarium equiseti on Grafted Watermelon in Korea

Abstract: In Korea, most of the grafted watermelons are a fusion of bottle gourd (Lagenaria siceraria) as a rootstock and watermelon (Citrullus lanatus) as a scionstock (Lee et al., 2010). Currently, we have collected several samples from grafted watermelon displaying symptoms of yellowing, withered and wilting leaves. When the symptomatic stem was excised, browning vascular tissues were observed due to the colonization of fungal pathogen. From the samples obtained, 25 fungal isolates were identified as species of Fusar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…According to the results, both fungal species can be regarded as causal agents of fruit rot disease in watermelons. Our results are supported by previous studies that reported that Fusarium species are the cause of various disease symptoms in watermelons in tropical and subtropical regions around the world [ 73 , 74 , 75 , 76 ]. Prior to this study, F. solani , F. oxysporum , F. verticillioides , and F. chlamydosporum were considered to be the causal agents of fruit rot in watermelons in Nigeria [ 16 , 24 , 77 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to the results, both fungal species can be regarded as causal agents of fruit rot disease in watermelons. Our results are supported by previous studies that reported that Fusarium species are the cause of various disease symptoms in watermelons in tropical and subtropical regions around the world [ 73 , 74 , 75 , 76 ]. Prior to this study, F. solani , F. oxysporum , F. verticillioides , and F. chlamydosporum were considered to be the causal agents of fruit rot in watermelons in Nigeria [ 16 , 24 , 77 ].…”
Section: Discussionsupporting
confidence: 92%
“…For example, F. equiseti and F. oxysporum f. sp. niveum have been observed to cause Fusarium wilt disease in fruits grown in Korea [ 76 ] and Malaysia [ 74 ], respectively. On the other hand, Fusarium brachygibbosum and F. oxysporum have been shown to lead to vine decline symptoms in the United States [ 73 ] and root rot in China [ 75 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…GJH-6, HYTZ-4, and HYTZ-4 strains with no conidia were con rmed as F. avenaceum, F. lateritium, and F. equiseti, respectively. F. equiseti was reported on rice in Argentina [26], barley in southern Europe [27], wheat in Iran [22], cumin in India [28], grafted watermelon in Korea [29], and peach fruit in Shanghai [7]. F. lateritium was reported on hazelnut fruit in Italy [30], Morus alaba var.…”
Section: Discussionmentioning
confidence: 99%
“…GJH-6 and SYGZ-1 with no conidia were confirmed as F. avenaceum , and F. equiseti , respectively. The F. equiseti was noted on rice in Argentina [ 26 ], barley in southern Europe [ 27 ], wheat in Iran [ 22 ], cumin in India [ 28 ], grafted watermelon in Korea [ 29 ], and peach fruit in Shanghai [ 7 ]. The F. lateritium was recorded on hazelnut fruit in Italy [ 30 ], Morus alba var.…”
Section: Discussionmentioning
confidence: 99%